Grupo de idosos enquanto dispositivo de empoderamento em saúde: uma proposta de pesquisa ação - Veras, Danielly Cristiny de (2019)
Population aging is a worldwide phenomenon. In this context, health policies, along with other public policies should promote that the increase in life expectancy is accompanied by quality, through actions that seek to provide equity and improve the conditions and ways of life of the elderly. Thus, health promotion groups are inserted as valuable health empowerment tools for the elderly. The objective was to develop actions in the field of health promotion and education in an elderly group and to understand how participation in the group contributed to health empowerment, from the perspective of the elderly. This is an exploratory study, with a qualitative approach based on the assumptions of action research, conducted with 26 elderly in a small population municipality of Paraíba. The activities were carried out through participatory and dialogical methodologies, from workshops and conversation circles, on themes from the elderly group. After these, 17 elderly were interviewed in order to understand their perceptions about health empowerment. The interviews were recorded and transcribed and analyzed according to the content analysis method. Data collection took place between September 2018 and March 2019, using a field diary and semi-structured interview. The empirical material was submitted to thematic analysis. The project was approved by the CAAE Research Ethics Committee: 93142418.4.0000.5188. The experience in the group according to the elderly influenced the health empowerment of the elderly and the quality of life in relation to the physical, psychological and social domains, leading them to evaluate the relationships between the members, the sharing of experiences and learning, reframing projects of health. stimulate autonomy and independence and satisfaction with health in old age, the result of a collective construction. By introducing a new look to the group where educators and learners became subjects throughout the process, it was possible to intervene politically in the struggle for health, as well as to articulate the educational process to the search for autonomy based on a participatory methodology that allowed the effective action of the students. participants in this process. The intervention valued the knowledge and experiences of all, facilitated discussion, identification and reflection on health and life problems, building meanings to the concrete situations of life. It is essential to support the elderly, professionals and managers to plan measures that promote improvements in health care for the elderly, more appropriate to the context of life and health of this population group.